2020
DOI: 10.1002/hed.26416
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of CD8/FOXP3 ratio combined with PD‐L1 expression for radiosensitivity in patients with squamous cell carcinoma of the larynx receiving definitive radiation therapy

Abstract: Background: Little is known about immune-related radiosensitivity in patients with squamous cell carcinoma of the larynx (SCC-L) treated with radiation therapy (RT). Methods: We retrospectively reviewed 91 patients with SCC-L treated with RT or chemoradiation therapy and performed immunohistochemical examination to analyze PD-L1 level on tumor cells, CD4 + tumor-infiltrating lymphocytes (TILs), CD8 + TIL, and FOXP3 + TIL using pretreated biopsy specimens. The association between these immune-related parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The studies that did not fulfill all the inclusion criteria were discarded. Of these, seven were excluded because they did not report the outcome of LSCC separately from other locations of HNSCC [12,[15][16][17][18][19][20], eight because no HRs were available [21][22][23][24][25][26][27][28][29], one study because they reported outcome in terms of local control [30], one study that evaluated Il-12R expression on tumor cells [31], and one study that evaluated lymphocytes in peripheral blood [32]. This left 11 studies for the analysis (Fig- Studies were selected if they met the following inclusion criteria: (1) prognostic value of TIL was evaluated in patients with LSCC (primary or recurrent), (2) TIL were evaluated either immunohistochemically (CD8+, CD4+, and/or CD3+) and/or in hematoxylin-and eosin (HE)-stained sections, in resected specimens or in diagnostic biopsies, (3) TIL were evaluated either in tumor epithelium and/or tumor stroma, (4) prognostic value of TIL was evaluated by time-to-event survival analysis with overall survival (OS) and/or disease-free survival (DFS), and (5) original articles published in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that did not fulfill all the inclusion criteria were discarded. Of these, seven were excluded because they did not report the outcome of LSCC separately from other locations of HNSCC [12,[15][16][17][18][19][20], eight because no HRs were available [21][22][23][24][25][26][27][28][29], one study because they reported outcome in terms of local control [30], one study that evaluated Il-12R expression on tumor cells [31], and one study that evaluated lymphocytes in peripheral blood [32]. This left 11 studies for the analysis (Fig- Studies were selected if they met the following inclusion criteria: (1) prognostic value of TIL was evaluated in patients with LSCC (primary or recurrent), (2) TIL were evaluated either immunohistochemically (CD8+, CD4+, and/or CD3+) and/or in hematoxylin-and eosin (HE)-stained sections, in resected specimens or in diagnostic biopsies, (3) TIL were evaluated either in tumor epithelium and/or tumor stroma, (4) prognostic value of TIL was evaluated by time-to-event survival analysis with overall survival (OS) and/or disease-free survival (DFS), and (5) original articles published in English.…”
Section: Resultsmentioning
confidence: 99%
“…The studies that did not fulfill all the inclusion criteria were discarded. Of these, seven were excluded because they did not report the outcome of LSCC separately from other locations of HNSCC [ 12 , 15 , 16 , 17 , 18 , 19 , 20 ], eight because no HRs were available [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], one study because they reported outcome in terms of local control [ 30 ], one study that evaluated Il-12R expression on tumor cells [ 31 ], and one study that evaluated lymphocytes in peripheral blood [ 32 ]. This left 11 studies for the analysis ( Figure 1 ) [ 9 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that it might be a useful biomarker of radiosensitivity in patients with laryngeal SCC receiving definitive RT. 39 In our study, most patients received RT, and the subset of PD-L1 þ patients could benefit from a combination of radiotherapy and anti-PD-L1 treatment. Further studies on CD8/FOXP3 expression on ASCC are needed to explore future therapeutic venues.…”
Section: Pd-l1 Expression and Outcomesmentioning
confidence: 82%
“…The numerical and functional abnormality of Tregs may be influenced by radiation dose, the form of radiation, or tumor type. 39,40 A previous study of HIV-positive patients with cervical squamous cell carcinoma showed that PD-L1 þ tumor cells are more radiosensitive and that those patients show better response with RT. 35 High CD8:FOXP3 ratio combined with negative PD-L1 expression was an independent and significant favorable predictive factor for local control.…”
Section: Pd-l1 Expression and Outcomesmentioning
confidence: 99%
“…Furthermore, we have shown that the density of tumor infiltrate within nasopharyngeal cancer tumor microenvironment was also associated with tumor progression [5]. Various data has indicated that the immune contexture within tumor microenvironment in most solid cancer has a great role predicting treatment outcomes [14][15][16][17][18]. For instance, higher density of infiltrating tumor T regulatory FOXP3 cells was shown to negatively affect prognosis in breast cancer [19].…”
Section: Introductionmentioning
confidence: 95%